ESTIMATION OF HETEROSIS FOR YIELD AND SOME YIELD COMPONENTS IN BREAD WHEAT (TRITICUM AESTIVUM L.) - VITTHAL D. GITE; ANANT R. MALI; BHANUDAS D. IDHOL; JUNED H. BAGWAN (The Bioscan, 2014)
Heterosis estimated over mid and better parents in 7 x 7 half diallel design for ten different cross combinations of bread wheat. The crosses were estimated for yield and yield contributing characters. The maximum heterobeltiosis was recorded for Productive tillers per plant (47.64%) and Weight of grains per spike (26.41%). The crosses DI9 x MP-4080, LOK-62 × PHS-0622, PHS-0622 × MP-4080 and DI-9 × PHS-0622 were identified as promising for many desirable traits and they may be useful in exploiting hybrid vigour. The data provides information on heterotic advantage of important yield and associated components. The highest heterotic genotypes can be exploited in future breeding programs to attain self-sufficiency in food grains. However, comprehensive field evaluation over locations and years is advocated for the crosses having significant heterosis before their commercial exploitation.